A study on crosses of oriental tobacco (Nicotiana tabacum L.) investigating genetic variation in yield, quality and drought tolerance - Hill, Merle Sharon (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1995.